The representation of the indigenous peoples of Mexico in Diego Rivera's National Palace mural, (1929-1935) - Picot, Natasha Mathilde (2007)
This thesis is a multidisciplinary project, drawing on the discourses of Visual Cultural Studies, Latin American history and Critical Theory. Insights from each of these disciplines interact to investigate the representation of the indigenous peoples of Mexico in the mural triptych entitled History of the Mexican People painted by Diego Rivera in the National Palace, Mexico City between 1929 and 1935. The main focus is an exploration of the mural as a cultural text, which is formed through socio-political structures and homogenising nationalist visions. The artist is seen as partly a product of history who acts, both consciously and subconsciously, as a conduit for such historical structures. The investigation requires a multi-dimensional approach as it includes emotional, aesthetic, sociological, political, cultural, philosophical, biographical and material elements.